Preparation of silver nanoparticles in aromatic leaves extract and ionic liquid for photodegradation of 2,4– dichlorophenoxyacetic acid - Nur Syahirah, Kamarudin (2019)
The 2,4–dichlorophenoxyacetic acid (2,4–D) herbicide used widely in the agricultural industry is the main toxic pollutant that has caused damage to the aquatic ecosystems and human health. Due to this, continuous research on the effectiveness of catalyst for degradation of this recalcitrant pollutant has been conducted in these recent years. In this study , silver (Ag) catalysts were synthesized and characterized via electrochemical methods in leaves extract and ionic liquid. The performance of the synthesized catalyst towards degradation of 2,4–D was investigated and optimized by Response Surface Methodology (RSM). The kinetic model and reusability of the synthesized photocatalyst were also studied. First, aromatic leaves were extracted using ultrasonic– assisted hydro–distillation (UAE–HD) method and classical aqueous extraction (AE). Then, Ag nanoparticles were synthesized by electrochemical methods with aromatic leaf extracts and ionic liquids as synthesis media. The catalysts were then characterized using X–ray diffraction (XRD), Scanning Electron Microscopy (SEM), Transmission electron microscopy (TEM), Fourier transform infrared (FTIR), Surface area analysis (BET), UV–vis diffuse reflectance spectra (UV–vis DRS) and Photoluminescence (PL) studies. Then, the photocatalytic activity of the catalyst was tested by degradation of 2,4–D. Furthermore, the optimization of the photocatalytic process was carried out by using Response Surface Methodology (RSM). The kinetic study of the photocatalytic reaction was also analyzed by first order, second order and Langmuir Hinshelwood. Lastly, the reusability study was conducted to determine the efficiency of the catalyst. The results indicated that UAE–HD method was able to yield a higher amount of phenolic content as compared to AE method. The results revealed that ionic liquids and phenolic compounds in leaf extract have synergistic effects to reduce silver ions (Ag + ) into zero–valent Ag nanoparticles and act as capping agents in the nanoparticles formation. Then, the performance of the catalysts was tested towards the photodegradation of 2,4–D in a batch reactor under visible light irradiation. The results showed that the Ag nanoparticles were able to inhibit electron–hole recombination to give a nearly complete degradation (96.54%) of 10 mg L -1 2,4–D at pH 3 when using 0.01 g L -1 of Ag catalyst prepared in 1–butyl–3–methylimidazolium bis(trifluoromethylsulfonyl) imide [BMIM Tf 2 N] ionic liquid and Orthosiphon stamineus (OS) leaves extract media extracted by UAE–HD method. It was found that high amount of phenolic content in leaf extract as well as a long alkyl chain of imidazolium cation and large structure of anion led to diminutive and discrete nanoparticles, which enhanced the photodegradation of 2,4–D. Besides, the existence of the phenolic compound and ionic liquid on the surface of the catalysts play important roles as electron acceptors that enhanced the electron–hole separation process. The response surface methodology (RSM) analysis of the catalysts showed a good significance of model with low probability values (<0.0001) and a high coefficient of determination (R 2 ) with 97.80% of the optimum percentage of 2,4–D degradation at pH 3.24, 0.009 g L -1 of Ag catalyst and 8.15 mg L -1 of 2,4–D concentration. The kinetic studies of the catalysts illustrated that the surface reaction was controlling the step of the process. A reusability study showed that catalysts were still stable after 4 subsequent reactions. Significantly, the synthesis method of the catalysts could be a great advantage in the future development of nanotechnology for degradation of various organic pollutants.